Analysis of Risk, Size, and Performance of the Banking Industry : A South Asian Perspective - Chakraborty, Brishti (Indian Journal of Finance, 2024)
Purpose : The article examined the correlation between risk factors, performance, capital regulation, and the banking industry, particularly emphasizing the moderating effect of size. It aimed to differentiate between healthy and hazardous companies and assess the financial stability of enumerated Asian banks, accounting for 60% of the global development. Methodology : The acceptability of the data for additional analysis was determined by the study using variance inflation factors, correlation analysis, and unit root tests. A two-stage least squares study of 25 universities was carried out using a panel dataset with unbalanced variables spanning the years 2014 to 2021. Findings : The study showed that, out of capital sufficiency, credit risk, and liquidity concerns, credit risk had the greatest impact on bank profitability (ROE). ROE was positively impacted by additional independent factors such as TCTA, LE, and AGE. Furthermore, a significant moderating effect of bank size on the relationship between risk and profitability was found, which had a negative impact on ROE for all risk categories. Practical Implications : Effective risk management is essential for the Asian financial sector in order to reduce losses, boost operational efficiency, guarantee regulatory compliance, and build confidence. Policymakers in Asian countries ought to establish a stable financial environment by providing incentives for interest rates to lower the amount of non-performing loans. To survive commercially in a highly competitive environment, one must have a strong position of liquidity. By broadening the field of inquiry, this work opens up possibilities for future researchers. Originality : An innovative model was developed to analyze the correlation between bank size and risk and performance within the financial sector of South Asia, using control variables, bank-specific measurements, and accounting-based metrics.